Assisted reproductive technology service availability, efficacy and safety in mainland China: 2016. Issue 2 (4th February 2020) - Bai, F; Wang, D Y; Fan, Y J; Qiu, J; Wang, L; Dai, Y; Song, L
Abstract: STUDY QUESTION: What is the current status of assisted reproductive technology (ART) service availability, efficacy and safety in mainland China? SUMMARY ANSWER: In this first national report on ART status in mainland China, data on treatment numbers, outcomes and complications in 2016 are provided and analyzed, respectively. WHAT IS KNOWN ALREADY: National ART Service Provision Surveys are conducted in mainland China regularly. Data were analyzed, and this manuscript was written by team members from the National Center for Women and Children's Health, China CDC and the Department of Women and Children Health, National Health Commission of the People's Republic of China. STUDY DESIGN, SIZE AND DURATION: A cross-sectional nationwide survey was completed in 2018, in which data regarding ART treatments, performed from 1 st January to 31 st December2016 in 445 ART clinics located in 31 provinces of mainland China, were collected. PARTICIPANTS/MATERIALS, SETTING AND METHODS: There were in total 451 licensed ART clinics (including artificial insemination clinics) in mainland China in 2016, of which 445 submitted service data. A total of 906 840 cycles were provided by 323 in vitro fertilization (IVF) clinics, involving 375 770 conventional IVF cycles, 154 948 intracytoplasmic sperm injection (ICSI) cycles, 367 146 frozen embryo transfer (FET) thawing cycles and 8976 preimplantation genetic diagnosis (PGD) treatment cycles. A total of 161 376 artificial (i.e. intrauterine) insemination (AI) cycles were reported by 443 clinics, with 126 872 cycles using the husband's semen (AIH) and 34 504 using donor semen (AID). MAIN RESULTS AND THE ROLE OF CHANCE: In total, 98.7% of the licensed clinics, contributing to 100% of the ART services (including AID and AIH cycles), were included in this report. (Six clinics provided institutional information only and were excluded.) There were 906 840 in vitro fertilization cycles performed in mainland China with a population of over 1.3 billion inhabitants, with cycles per million inhabitants (C/M) increasing from 360 in 2013 to 657 in 2016, nationwide (range among provinces: 45–3676). After treatment with conventional IVF, the clinical pregnancy rate (PR) per oocyte retrieval cycle was 23.2%, the delivery rate (DR) per oocyte retrieval cycle was 18.7% and the proportion of twin delivery among the total deliveries was 27.9%. For ICSI cycles, the PR, DR and TDR were 20.5%, 16.7% and 27.2%, respectively. For FET per thawing cycles, the PR, DR and TDR were 48.2%, 37.6% and 24.2%. For PGD per diagnosis cycles, the PR, DR and TDR were 38.1%, 29.7% and 4.2%. For AIH cycles, the PR and DR were 13.3% and 10.5%; for AID cycles, the PR and DR were 24.3% and 21.1%, respectively. The total number of live infants born in mainland China in 2016, was 18.46 million, and the number of infants born through ART conducted in 2016 was 311 309, which accounted for 1.69% of the total. The reported rate of birth defects was about 87/10 000. The incidence of moderate to severe ovarian hyper-stimulation syndrome (OHSS) was 11.5 per 1000 oocyte retrieval cycles, and other complications were much more rare. LIMITATIONS AND REASONS FOR CAUTION: This report is based on the summary data of ART services provided. The success rates were not calculated by age stratification. A low rate of birth defects was reported, which might be confounded by variations in birth follow-up methods, statistical timing and record taking. WIDER IMPLICATIONS OF THE FINDINGS: ART service availability has improved significantly in recent years in mainland China. Because China is a vast country, significant imbalances in ART service provision do exist; however, the main efficacy and safety indicators were close to those of western countries. TRIAL REGISTRATION NUMBER: N/A STUDY FUNDING/COMPETING INTEREST(S): The study was funded by the National Key R&D Program of China (2016YFC1000307–2). There are no competing interests.